Managing projects as investments earned value to business value - Devaux, Stephen A. 1949- (Industrial innovation series, 2014)
Due to a lack of appreciation of the true economic identity of projects, techniques and metrics that could hugely improve project selection and performance are not being used. This book provides insights and innovative techniques drawn from more than a quarter century of experience